Experimental investigations on concrete incorporated with calcined hydrotalcite under sea water curing. (2022) - Vincent Venkatesan, P.; Suganya, R.; Revathi, S.
Abstract: In this study, Calcined Hydrotalcite is used in concrete to facilitate seawater curing. The salts from seawater penetrate into the concrete which lowers the strength of the concrete when cured in sea water. Also, these salts attack the reinforcement of RC elements causing corrosion of steel. Hydrotalcite is a layered double hydroxide which resembles talc and has high water content. Calcined hydrotalcite has higher adsorption capacity and can be used for adsorption. Calcined hydrotalcite has been prepared by grinding method. It has been synthesised from Aluminium Oxide, Magnesium Hydroxide, and Sodium Bicarbonate by heating at 100 °C. The Calcined Hydrotalcite thus synthesised and added to concrete in proportions. Then, when this concrete has been cured in sea water, the anions in the seawater were adsorbed by the added calcined hydrotalcite. Thus, the strength of the concrete element is retained even when cured in sea water.